Alliance in the agroindustrial system of coffee: Alliance model for adding value to coffee certificates - Aguiar, Cibele Maria Guarcia de; Carvalho, Nádia; Pereira, Sérgio Parreiras; Sugano, Joel Yutaka (Coffee Science - ISSN 1984-3909, 2012)
With the emergence of the digital economy, alliances dynamics of cooperation between different sectors have beenconsidered as the organizational format appropriate to promote the generation and transference of knowledge and innovations. Thesechanges also occur in the coffee agribusiness system, and Minas Gerais seeks to add value to products through certification andintegration between sectors. Based on this interaction, we analyzed the participants’ perceptions of the program Certifica Minas Caféand Cafés Sustentáveis of the ABIC, regarding integration synergies in government, universities and companies, identifying the roleof coordination and communication in a new business model. The exploratory research involved the application of survey questionnairesamong sectors of the Alliance: production, extension and industry. The data analysis was performed on SPSS software, and theobservations and documentary collections were incorporated in the analysis. In conclusion, it appears that there is synergy inintegrating government, universities and businesses, setting up a complementary relationship in an innovative business model, beingreserved for each link that would not be likely benefits of the traditional pattern of trade. However, they point to bottlenecks incommunication channels, suggesting to the alliance’ managers attention that the flow of information be intensified among the threespheres. During this analysis, the communication model adopted did not encourage the integration of all participants; a feature that,over time, instead of creating synergies, could result in a disorder in the relations caused by an overflow of information.